ANALISIS KESALAHAN PESERTA DIDIK DALAM MENYELESAIKAN SOAL MATEMATIKA - HAMFARO DHERMAWIN (Jurnal Edukasi dan Penelitian Matematika, 2018)
The aim of this research is to describe types of errors, the factors of students’ errors, and solution to minimize the errors in solving the mathematical problem about Cartesian coordinates. The types of errors are categorized based on Kastolan. The approach in this research was qualitative approach with a type of descriptive research. The techniques of data collection in this research were test and interview. Data validation was done by triangulation by comparing the result of test data and interview. The technique of data analysis was done by data reduction, data presentation, and data verification. The subjects of this research were the students class VIII.1 SMP Negeri 6 Padang.   The result of this research indicated that (1) The students made a conceptual error about 45% because they did not comprehend the question, could not comprehend the concept well, could not apply the concept, could not  understand the material that have been studied before. (2) The students made a procedural error about 31% because they could not complete the test based on appropriate procedures, unskilled in solving the problem by writing the procedures of completion, not reading the questions well, and lack of time when doing the test. (3)The students made a technical error about 24% because they were not checking the answers before they were collected, not yet mastering the algebraic operations, not being careful in carrying out the calculation operations of the counting operations. The solution to minimize students’ errors can be done by providing the varieties of learning model. In this case, the learning model that provided is cooperative model STAD type, which shows that this can minimize students' error. Keyword: Students’ errors, cartesian coordinates, errors by Kastol’s category, cooperative model STAD type